Analysis of Fixed Asset Accounting Treatment Based on Psak No.16 at Pt Buana Finance Tbk Bengkulu Branch - Selly Marselina; Yun Fitriano; Abdul Rahman (UNIVED Press, 2024)
Assets in general are resources controlled by a company as a result of past events, where future economic benefits are expected to flow to the company. Fixed assets are part of the assets owned by the company to be used in company operations where payments will change at any time due to depreciation. This study aims to determine whether the accounting treatment of fixed assets in a company starting from recognition, disbursement after acquisition, depreciation, termination and delivery of fixed assets at PT Buana Finance Tbk, is in accordance with PSAK No.16. The analytical method used is descriptive method with data collection techniques in the form of interviews to obtain data in the form of fixed asset accounting treatment. The results of the study show that the accounting treatment for fixed assets applied by the company PT Buana Finance Tbk is in accordance with the Statement of Financial Accounting Standards (PSAK) No. 16 Fixed Assets